STRATEGI KOMUNIKASI PEMASARAN THE MANGLUNG DI TENGAH MARAKNYA RESTO BERNUANSA CAFE DI YOGYAKARTA - Utari, Tariza; Wenerda, Indah (Komodifikasi, 2019)
Nowadays the restaurant business is no longer just about selling food or beverage flavors to customers. Therefore the restaurant business is also expected to be able to look as creative as possible in providing facilities, such as providing a different concept from other restaurants that make consumers interested and want to visit it. Social media has an important role in the world of digital marketing because it can help a product or brand become more easily recognized by the public. Social media also brings many benefits such as easy use, can be accessed anytime, anywhere and also cost-effective. Not only social media, promotional media through word of mouth also has an important role that can increase sales. In this thesis researchers used a qualitative research method with the type of descriptive study. The subjects in this study are the owner who is an important source of information for The Manglung View and Resto and also the customers who are customers in this restaurant. While the object in this study is the importance of conducting communication strategies to increase visitor attractiveness and to meet customer satisfaction. This research was conducted by collecting data through observation, in-depth interviews, and documentation. Then based on the data that has been found then researchers describe the results descriptively. The results of this study indicate that, the efforts made by The Manglung View and Resto in creating a communication strategy amid the rise of cafe nuances in Yogyakarta are good enough, but there are still some things that need to be improved and further improved in the future to meet consumer desires.